Regional Strategic Planning using Fuzzy Cognitive Maps - Penni, Lynnette Eyram (Univerzita Pardubice, 2018)
In this research, the use of Fuzzy cognitive map (FCM) is adopted to simulate the strategic goals of the Rural Enterprise Development Program (REP). FCM creates models as collection of concepts and the various casual relationships that exist between these concepts. The scenarios proposed by the Expert of the organization is being examined dynamically through simulations using this FCM hence the design and implementation of FCM for REP and their current approaches to regional strategic planning. Drawing on approaches to regional strategic planning in Ghana in the field of rural enterprise development. Interviews with the Expert of the REP in the Hohoe Municipal Assembly of the Volta Region and simulation results clearly identifies and argues concepts such as Youth in Apprenticeship, Business Counselling and Access to Rural Finance as main drivers in the economic development and draws out series of recommendations concerning a wider policy implication of the study.
Regionální strategické plánování pomocí fuzzy kognitivních map
Keywords: fuzzy cognitive maps; regional strategic planning; Rural Enterprise Development; fuzzy kognitivní mapy; regionální strategické plánování; Program rozvoje venkova